Sodium MRI in multiple sclerosis is compatible with intracellular sodium accumulation and inflammation-induced hyper-cellularity of acute Brain Lesions - Biller, Armin; Pflugmann, Isabella; Badde, Stephanie; Diem, Ricarda; Wildemann, Brigitte; Nagel, Armin Michael; Jordan, J.; Benkhedah, Nadia; Kleesiek, Jens Philipp (Scientific reports, 2016)
The cascade of inflammatory pathogenetic mechanisms in multiple sclerosis (MS) has no specific conventional MRI correlates. Clinicians therefore stipulate improved imaging specificity to define the pathological substrates of MS in vivo including mapping of intracellular sodium accumulation. Based upon preclinical findings and results of previous sodium MRI studies in MS patients we hypothesized that the fluid-attenuated sodium signal differs between acute and chronic lesions. We acquired brain sodium and proton MRI data of N = 29 MS patients; lesion type was defined by the presence or absence of contrast enhancement. N = 302 MS brain lesions were detected, and generalized linear mixed models were applied to predict lesion type based on sodium signals; thereby controlling for varying numbers of lesions among patients and confounding variables such as age and medication. Hierarchical model comparisons revealed that both sodium signals average tissue (χ2(1) = 27.89, p < 0.001) and fluid-attenuated (χ2(1) = 5.76, p = 0.016) improved lesion type classification. Sodium MRI signals were significantly elevated in acute compared to chronic lesions compatible with intracellular sodium accumulation in acute MS lesions. If confirmed in further studies, sodium MRI could serve as biomarker for diagnostic assessment of MS, and as readout parameter in clinical trials promoting attenuation of chronic inflammation.
Gesehen am 12.05.2020